Long-term hominin preference for the gallery forest edge: Insights from the Gona paleosols, Afar, Ethiopia - Stinchcomb, Gary E.; Rogers, Michael J.; Semaw, Sileshi (Quaternary Science Reviews, 2025)
The Gona Paleoanthropological Research Project area in the Afar Region of Ethiopia arguably contains one of the most complete records of archaeological sites anywhere in the world, from the earliest Oldowan dated to 2.6 Ma, to the Later Stone Age (LSA) dated to ca. 12-7 Ka. This makes Gona an ideal place to examine long-term trends in hominin-environment interaction. We revisited archaeological and hominin fossil sites at Gona and characterized the fossil soils using paleopedology and found evidence of paleo-Fluvisols, -Cambisols and -Vertisols. Greater than 70% of those archaeological sites spanning Oldowan to the Later Stone Age are found in buried paleosols with A-C and A-Bk-C paleosol profiles resembling modern-day Fluvisols or Fluvic Cambisols. Fluvisol morphology shows presence of bedding, incipient soil structure development and overprinting after burial. Stratigraphy and lithofacies show that these paleo-Fluvisols were proximal to the ancestral Awash River (Type I depositional system) or a distal fan channel (Type II depositional system). These data suggest that soil burial rates were rapid due to proximal flooding, where this would be a primary factor inhibiting soil development. This style of sedimentation and weathering resembles a narrow (5–10 m width) strip of land in a modern-day channel shelf and bar setting, separating the river from the adjacent gallery forest. A review of the literature shows that the frequent association of artifacts with paleo-Fluvisols may be prevalent throughout eastern Africa and indicates a long history of hominin reliance on a riverine ecosystem edge, proximal stream water and gallery forest resources within broader river valleys. The few older archaeological sites (e.g., Oldowan and Acheulian) found in/on more well-developed paleosols at Gona are an exception to this rule. These latter sites may hint at different land-use patterns and thus differing trajectories of hominin-environmental interactions. Because most paleosol studies at Gona and elsewhere in eastern Africa use paleo-Vertisols or other more well-developed calcareous soils to reconstruct paleoenvironment, there is a potential spatial and temporal decoupling between those well-studied paleosols and the more weakly-developed ones where archaeology is found.
Keywords: Archaeology; Artificial intelligence; Astronomy; Computer science; Enhanced Data Rates for GSM Evolution; Geography; Geology; Gona; Mathematics; Paleoecology; Paleontology; Paleosol; Physics; Preference; River corridors; Statistics; Term (time); dept.ant; peer-reviewed

Paleoenvironments of Gona, Ethiopia, between 3-1 Mya: Evidence from faunal analysis - Leiss, Amanda C.; Rogers, Michael J.; Semaw, Sileshi (American Journal of Physical Anthropology, 2020)
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Reconstruction and analysis of the DAN5/P1 and BSN12/P1 Gona Early Pleistocene Homo fossils - Baab, Karen L.; Rogers, Michael; Bruner, Emiliano; Semaw, Sileshi (Journal of Human Evolution, 2022)
Two Early Pleistocene fossils from Gona, Ethiopia, were originally assigned to Homo erectus, and their differences in size and robusticity were attributed to either sexual dimorphism or anagenetic evolution. In the current study, we both revisit the taxonomic affinities of these fossils and assess whether morphological differences between them reflect temporal evolution or sexual variation. We generated virtual reconstructions of the mostly complete ∼1.55 Ma DAN5/P1 calvaria and the less complete 1.26 Ma BSN12/P1 fossil, allowing us to directly compare their anterior vault shapes using landmark-based shape analysis. The two fossils are similar in calvaria shape to H. erectus and also to other Early Pleistocene Homo species based on a geometric morphometric analysis of calvaria landmarks and semilandmarks. The DAN5/P1 fossil bears a particularly close affinity to the Georgian H. erectus fossils and to KNM-ER 1813 (H. habilis), probably reflecting allometric influences on vault shape. Combined with species-specific traits of the neurocranium (e.g., midline keeling, angular torus), we confirm that these fossils are likely early African H. erectus. We calculated regression-based estimates of endocranial volume for BSN12/P1 of 882–910 cm3 based on three virtual reconstructions. Although BSN12/P1 is markedly larger than DAN5/P1 (598 cm3), both fossils represent the smallest adult H. erectus known from their respective time periods in Africa. Some of the difference in endocranial volume between the two Gona fossils reflects broader species-level brain expansion from 1.77 to 0.01 Ma, confirmed here using a large sample (n = 38) of H. erectus. However, shape differences between these fossils did not reflect species-level changes to calvaria shape. Moreover, the analysis failed to recover a clear pattern of sexually patterned size or shape differences within H. erectus based on our current assessments of sex for individual fossils.
Keywords: Africa; Animals; Biological Evolution; Brain; Brain evolution; Calvaria shape; Ethiopia; Fossils; Hominidae; Homo erectus; Intraspecific variation; Pleistocene; Sexual dimorphism; Skull; anatomy and histology; animal; brain; dept.ant; evolution; fossil; hominid; human evolution; intraspecific variation; morphology; peer-reviewed; reconstruction; sexual dimorphism; skull; temporal evolution

Imposed Form in the Early Acheulean? Evidence from Gona, Afar, Ethiopia - Stout, Dietrich; Liu, Cheng; Muller, Antoine; Rogers, Michael; Semaw, Sileshi (Journal of Archaeological Method and Theory, 2025)
Keywords: Acheulean; Ancient history; Anthropology; Archaeology; Early Stone Age; Ethnology; Geography; Handaxe; History; Large cutting tool; Lithic technology; Pick; Pleistocene; Shaping; Sociology; dept.ant

New reconstruction of DAN5 cranium (Gona, Ethiopia) supports complex emergence of Homo erectus - Baab, Karen; Kaifu, Yousuke; Freidline, Sarah; Rogers, Michael; Semaw, Sileshi (Nature Communications, 2025)
The African Early Pleistocene is a time of evolutionary change and techno-behavioral innovation in human prehistory that sees the advent of our own genus, Homo, from earlier australopithecine ancestors by 2.8-2.3 million years ago. This was followed by the origin and dispersal of Homo erectus sensu lato across Africa and Eurasia between ~ 2.0 and 1.1 Ma and the emergence of both large-brained (e.g., Bodo, Kabwe) and small-brained (e.g., H. naledi) lineages in the Middle Pleistocene of Africa. Here we present a newly reconstructed face of the DAN5/P1 cranium from Gona, Ethiopia (1.6-1.5 Ma) that, in conjunction with the cranial vault, is a mostly complete Early Pleistocene Homo cranium from the Horn of Africa. Morphometric analyses demonstrate a combination of H. erectus-like cranial traits and basal Homo-like facial and dental features combined with a small brain size in DAN5/P1. The presence of such a morphological mosaic contemporaneous with or postdating the emergence of the indisputable H. erectus craniodental complex around 1.6 Ma implies an intricate evolutionary transition from early Homo to H. erectus. This finding also supports a long persistence of small-brained, plesiomorphic Homo group(s) alongside other Homo groups that experienced continued encephalization through the Early to Middle Pleistocene of Africa. The origin and dispersal of Homo erectus, a long-lived and geographically widespread human ancestor, are unclear despite a rich fossil record. Here, the authors reconstruct the face from a Homo erectus cranium from Gona, Ethiopia, dated to 1.5-1.6 million years ago, providing insights into the evolutionary transition from early Homo to H. erectus.
Keywords: Crania; Early Pleistocene; Hominidae; Homo erectus; Human evolution; Pleistocene; Sensu; Skull; dept.ant

The endocast from Dana Aoule North (DAN5/P1): A 1.5 million year-old human braincase from Gona, Afar, Ethiopia - Bruner, Emiliano; Holloway, Ralph; Baab, Karen L.; Rogers, Michael J.; Semaw, Sileshi (American Journal of Biological Anthropology, 2023)
The nearly complete cranium DAN5/P1 was found at Gona (Afar, Ethiopia), dated to 1.5–1.6 Ma, and assigned to the species Homo erectus. Its size is, nonetheless, particularly small for the known range of variation of this taxon, and the cranial capacity has been estimated as 598 cc. In this study, we analyzed a reconstruction of its endocranial cast, to investigate its paleoneurological features. The main anatomical traits of the endocast were described, and its morphology was compared with other fossil and modern human samples. The endocast shows most of the traits associated with less encephalized human taxa, like narrow frontal lobes and a simple meningeal vascular network with posterior parietal branches. The parietal region is relatively tall and rounded, although not especially large. Based on our set of measures, the general endocranial proportions are within the range of fossils included in the species Homo habilis or in the genus Australopithecus. Similarities with the genus Homo include a more posterior position of the frontal lobe relative to the cranial bones, and the general endocranial length and width when size is taken into account. This new specimen extends the known brain size variability of Homo ergaster/erectus, while suggesting that differences in gross brain proportions among early human species, or even between early humans and australopiths, were absent or subtle.
Keywords: Homo erectus; Homo ergaster; Lower Pleistocene; brain evolution; dept.ant; human evolution; paleoneurology; peer-reviewed

Paleoenvironmental changes during the last 6 million years at Gona, Afar Region, Ethiopia - Levin, Naomi E; Simpson, S.; Rogers, Michael J.; Semaw, S. (African Paleoecology and Human Evolution, 2020)
Keywords: dept.ant

Gona, Ethiopia: microcosm of the stone age - Rogers, Michael J.; Semaw, Sileshi; Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Cauche, Dominique (Handbook of Pleistocene Archaeology of Afric, 2023)
The Gona paleoanthropological field project in the Afar region of Ethiopia has long been associated with the earliest Oldowan stone tools. However, over the last 20 years, ongoing research at Gona has expanded its contributions considerably, producing fossils of Ardipithecus kadabba, Ardipithecus ramidus, and Homo erectus, as well as additional archaeological evidence of the earliest Oldowan and early Acheulean. Moreover, in the last few years, the Gona team has turned its attention to the younger deposits exposed in its study area and discovered a surprising number of Middle Stone Age (MSA) and Later Stone Age (LSA) archaeological sites, mostly from the Late Pleistocene to the early-middle Holocene. While any sedimentary sequence is incomplete by virtue of episodic depositional and erosional events over time, we are struck by the relative completeness of the archaeological sequence at Gona (Quade et al., 2008). The hominin fossils attract deserved attention, but the Gona project may ultimately be best known for preserving arguably the most extensive, detailed, and continuous Stone Age or Paleolithic archaeological sequence in the world, all contained within a small 25 km × 10 km area, approximately half of the total project area.
Keywords: dept.ant

Fossil Cercopithecidae from the Early Pliocene Sagantole Formation at Gona, Ethiopia - Frost, Stephen R.; Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael J.; Semaw, Sileshi (Journal of Human Evolution, 2020)
The Early Pliocene Sagantole Fm. in the Gona Project area, Afar State, Ethiopia, is noted for discoveries of the early hominin Ardipithecus ramidus. A large series of fossil cercopithecid primates dated to between 4.8 and 4.3 Ma has also been collected from these sediments. In this paper, we use qualitative analysis and standard dental and postcranial measures to systematically describe the craniodental remains and tentatively allocate postcrania to taxa where we are able to. We then use these data to compare these specimens to fossil assemblages from contemporary sites, interpret their paleobiology, and discuss implications for the paleoecology of the Gona Sagantole Fm. We recognize three cercopithecid species in the Gona Sagantole Fm. Pliopapio alemui makes up approximately two-thirds of the identifiable specimens; nearly all of the rest are allocated to Kuseracolobus aramisi, and a single molar indicates the presence of a second, somewhat larger but morphologically distinct papionin. Among the Early Pliocene cercopithecids from Gona are also a number of postcranial elements. None of the postcranial remains are directly associated with any of the cranial material. Nonetheless, some of the distal humeri and proximal femora can be tentatively allocated to either Pl. alemui or K. aramisi based on a combination of size, as the latter is approximately 50% larger than the former, and morphology. If these assignments are correct, they suggest K. aramisi was primarily arboreal and similar to most extant colobines, whereas Pl. alemui was more mixed in its substrate use, being more terrestrially adapted than K. aramisi, but less so than extant Papio or Theropithecus. Thus, we interpret the predominance of Pl. alemui over K. aramisi is consistent with a somewhat more open environment at Gona than at Aramis. © 2020 Elsevier Ltd
Keywords: Animals; Ardipithecus ramidus; Cercopithecidae; Ethiopia; Female; Fossils; Gona; Kuseracolobus; Life History Traits; Male; Paleobiology; Papio; Pliocene; Pliopapio; Primates; Theropithecus; anatomy and histology; animal; cranium; dentition; dept.ant; female; fossil; fossil assemblage; hominid; life history trait; male; paleobiology; paleoecology; peer-reviewed; physiology; qualitative analysis; taxonomy

Estimating sexual size dimorphism in fossil species from posterior probability densities - Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Beyene, Yonas; Asfaw, Berhane; White, Tim D.; Suwa (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Accurate characterization of sexual dimorphism is crucial in evolutionary biology because of its significance in understanding present and past adaptations involving reproductive and resource use strategies of species. However, inferring dimorphism in fossil assemblages is difficult, particularly with relatively low dimorphism. Commonly used methods of estimating dimorphism levels in fossils include the mean method, the binomial dimorphism index, and the coefficient of variation method. These methods have been reported to overestimate low levels of dimorphism, which is problematic when investigating issues such as canine size dimorphism in primates and its relation to reproductive strategies. Here, we introduce the posterior density peak (pdPeak) method that utilizes the Bayesian inference to provide posterior probability densities of dimorphism levels and within-sex variance. The highest posterior density point is termed the pdPeak. We investigated performance of the pdPeak method and made comparisons with the above-mentioned conventional methods via 1) computergenerated samples simulating a range of conditions and 2) application to canine crown-diameter datasets of extant known-sex anthropoids. Results showed that the pdPeak method is capable of unbiased estimates in a broader range of dimorphism levels than the other methods and uniquely provides reliable interval estimates. Although attention is required to its underestimation tendency when some of the distributional assumptions are violated, we demonstrate that the pdPeak method enables a more accurate dimorphism estimate at lower dimorphism levels than previously possible, which is important to illuminating human evolution. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Bayes Theorem; Bayes theorem; Cuspid; Female; Fossils; Male; Models; Sex Characteristics; Statistical; animal; article; attention; canine tooth; controlled study; dept.ant; female; fossil; human; human experiment; intermethod comparison; male; nonhuman; peer-reviewed; primate; probability; sex difference; sexual characteristics; statistical model

Canine sexual dimorphism in Ardipithecus ramidus was nearly human-like. - Suwa; Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Kunimatsu, Yutaka; Nakatsukasa, Masato; Kono, Reiko T.; Zhang, Yingqi; Beyene, Yonas; Asfaw, Berhane; White, Tim D. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Body and canine size dimorphism in fossils inform sociobehavioral hypotheses on human evolution and have been of interest since Darwin’s famous reflections on the subject. Here, we assemble a large dataset of fossil canines of the human clade, including all available Ardipithecus ramidus fossils recovered from the Middle Awash and Gona research areas in Ethiopia, and systematically examine canine dimorphism through evolutionary time. In particular, we apply a Bayesian probabilistic method that reduces bias when estimating weak and moderate levels of dimorphism. Our results show that Ar. ramidus canine dimorphism was significantly weaker than in the bonobo, the least dimorphic and behaviorally least aggressive among extant great apes. Average male-to-female size ratios of the canine in Ar. ramidus are estimated as 1.06 and 1.13 in the upper and lower canines, respectively, within modern human population ranges of variation. The slightly greater magnitude of canine size dimorphism in the lower than in the upper canines of Ar. ramidus appears to be shared with early Australopithecus, suggesting that male canine reduction was initially more advanced in the behaviorally important upper canine. The available fossil evidence suggests a drastic size reduction of the male canine prior to Ar. ramidus and the earliest known members of the human clade, with little change in canine dimorphism levels thereafter. This evolutionary pattern indicates a profound behavioral shift associated with comparatively weak levels of male aggression early in human evolution, a pattern that was subsequently shared by Australopithecus and Homo. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Australopithecus; Bayes Theorem; Bayes theorem; Biological Evolution; Cuspid; Ethiopia; Female; Fossils; Hominidae; Humans; Male; Models; Pan paniscus; Phylogeny; Sex Characteristics; Theoretical; adult; aggression; anatomy and histology; animal; article; canine tooth; cladistics; classification; dept.ant; evolution; female; fossil; hominid; human; male; mandibular canine; maxillary canine; nonhuman; peer-reviewed; phylogeny; sex difference; sexual characteristics; theoretical model

Co-occurrence of Acheulian and Oldowan artifacts with Homo erectus cranial fossils from Gona, Afar, Ethiopia. - Semaw, Sileshi; Rogers, Michael J; Simpson, Scott W; Levin, Naomi E; Quade, Jay; Dunbar, Nelia; McIntosh, William C; Caceres, Isabel; Stinchcomb, Gary E; Holloway, Ralph L; Brown, Francis H; Butler, Robert F; et al. (Science advances, 2020)
Although stone tools generally co-occur with early members of the genus Homo, they are rarely found in direct association with hominins. We report that both Acheulian and Oldowan artifacts and Homo erectus crania were found in close association at 1.26 million years (Ma) ago at Busidima North (BSN12), and ca. 1.6 to 1.5 Ma ago at Dana Aoule North (DAN5) archaeological sites at Gona, Afar, Ethiopia. The BSN12 partial cranium is robust and large, while the DAN5 cranium is smaller and more gracile, suggesting that H. erectus was probably a sexually dimorphic species. The evidence from Gona shows behavioral diversity and flexibility with a lengthy and concurrent use of both stone technologies by H. erectus, confounding a simple "single species/single technology" view of early Homo. Copyright © 2020 The Authors, some rights reserved; exclusive licensee American Association for the Advancement of Science. No claim to original U.S. Government Works. Distributed under a Creative Commons Attribution NonCommercial License 4.0 (CC BY-NC).
Keywords: *Biological Evolution; *Fossils; *Hominidae; *Skull/ah [Anatomy & Histology]; Animals; Archaeological site; Behavioral diversity; Biodiversity; Biological Evolution; Co-occurrence; Ethiopia; Fossils; Hominidae; Hominidae/ah [Anatomy & Histology]; Hominidae/cl [Classification]; Hominins; Homo erectus; Humans; Paleontology; Single species; Skull; anatomy and histology; animal; classification; dept.ant; evolution; fossil; hominid; human; paleontology; peer-reviewed; skull

Fluvial response to Quaternary hydroclimate in eastern Africa: Evidence from Gona, Afar, Ethiopia - Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Iverson, Nels; Dunbar, Nelia; McIntosh, William; Arnold, Lee J.; Demuro, Martina; Duval, Mathieu; Grün, Rainer; Zhao, Jian-xin; White, Marie; et al. (Quaternary Science Reviews, 2023)
The Busidima Formation in the Afar region, Ethiopia, spans the Quaternary and records the cultural evolution of the genus Homo. Yet, the Middle Pleistocene to Holocene fluvial environments in which early humans lived are undersampled in eastern Africa. This paper examines the stratigraphy, geochronology and paleoenvironments of the newly designated Odele Member of the uppermost Busidima Formation (<152 thousand years ago (ka)), which has received little attention despite representing a critical period in the evolution of early Homo sapiens and its migration out of Africa. The Odele Member is 40–50 m thick and is dated using tephrochronology, radiometric, luminescence, and electron spin resonance techniques. The member spans 151 to 7 ka, defined at the base by the widespread Waidedo Vitric Tuff (WAVT, 151 ± 16 ka modeled age and 95.4% credible interval - C.I.). There are two prominent erosional unconformities in the Odele Member, a lower one after the WAVT deposition with a modeled 95.4% C.I. range of 124–97 ka; and an upper one involving widespread alluvial fan incision commencing between 21.7 and 12.9 ka. The uppermost Odele Member also contains black, organic-rich mats, redox features, reed casts, and freshwater gastropods marking wetter conditions during the terminal Pleistocene and Early Holocene. A black, fine-grained relict soil coeval with the Halalalee paleosol bounds the top of the Odele Member and has mollic and vertic properties, weathering since ∼12 ka. These incision events and prominent paleosol development near/at the top of the Busidima Formation document Middle to Late Pleistocene Awash River incision to its present-day course. Paleo-rainfall estimates suggest that the Early Holocene-age Halalalee paleosol weathered under a climate with mean annual rainfall 10–15% higher than today. A compilation of radiocarbon ages from aquatic gastropods, carbonized wood and charcoal from the upper Odele Member shows wetter and possibly more vegetated conditions during late marine isotope stage (MIS) 3 and the African Humid Period (AHP) that are tightly coupled with precession-driven summer insolation maxima. These key findings suggest that periods of incision, aggregation, and landscape stability in the Odele Member have an orbital precession pacing. The Odele Member revises upward the age of the Busidima Formation to 7 ka, showing that it spans into the Holocene and now includes Middle and Later Stone Age archaeological traditions.
Keywords: Electron spin resonance; Ethiopian rift; Fluvial aggradation; Fluvial incision; Paleosol; Radiocarbon; Tephrochronology; U-series; dept.ant; pIR-IRSL; peer-reviewed